Judeoconversos de Jerez y el obispado de Cádiz a fines del siglo XV. Conversos from Jerez and the Bishopric of Cadiz at the end of the 15th century - Gonzalo Carrasco García (En la España Medieval, 2006)
Many of the conversos of Jerez and the Bishopric of Cadiz, among other places, were affected by social rehabilitation measures at the end of the fifteenth century. This often took place after having been summoned by the Inquisition due to a previous sentencing of a family member. The statistical study of the rehabilitation lists (1495-1497) allows not only for an understanding of the sentences that befell this harassed group, but also reveals social trends in the converso collective of southern Andalusia. The converso community comes to light by way of a thorough onomastic, geographical, family and labour study. The result is an initial sketch of this group with certain sociological patterns that at times reinforce previous research on this matter, and at times point towards new hypotheses that reveal the complexity of converso society at the brink of the Modern Age.